ANALYSIS OF THE ACCOUNTING VERSES IN THE QUR'AN (International Conference on Social and Islamic Studies, 2022)
This study discusses the contribution of accounting in Islam in the semiotic analysis of the Qur'an. As for the motivation that drivesthe selection of accounting issues so far has only been considered as a tool to satisfy the owners of financial capital even though there are many satisfaction versesAl-Qur'an which discusses much more natural about accounting in Islam. Islam is sourced from the Qur'an Al Karim in many versestalk about things and the Qur'an. Analysis of verses of the Qur'anwhich contains the idea of ​​Islamic accounting needs to be analyzed from various scientific disciplinesAl-Qur'an and Al-Qur'an linguistics. One of the tools that can be used to analyze the text of the Qur'an is semiotics. Semiotics is an Islamicdiscusses signs and markers in communication. In studyand research to apply how semiotic theory is applied totrying to analyze linguistic signs regarding accounting in AlAl-Qur'an.